The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1994
DOI: 10.3133/ofr94276
|View full text |Cite
|
Sign up to set email alerts
|

Fate and pathways of injection-well effluent in the Florida Keys

Abstract: Conclusions 7 5 Suggestions for Future Studies 7 Acknowledgments References 7 Appendix A 29. Schematic geologic cross section of middle Key Largo and bar graph of major nutrient concentrations 69 30. Schematic geologic cross section of upper Key Largo and bar graph of major nutrient concentrations 7 0 IV Florida reef tract. Grainstone is approximately an order of magnitude less permeable than the coralline Key Largo Limestone facies. The Q3 surface, a major subsurface unconformity thought to form an effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1

Year Published

1996
1996
2005
2005

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(51 citation statements)
references
References 15 publications
2
48
1
Order By: Relevance
“…The nearshore reefs occur less than 5 km offshore and often experience extremely turbid waters. Although waters close to the Florida Keys tend to be slightly elevated in their nutrient concentrations and, based on the studies by Shinn et al (1994) and Lapointe et al (1990), might be expected to be affected by sewage derived from the Florida Keys, by 0.5 km, it has been shown that the nutrient concentrations of the reefal water are close to open marine conditions (Szmant and Forrester 1996). If the ␦ 15 N of organisms, such as corals, can be considered to be valid indicators of anthropogenic influence on the marine environment, then the data presented in this paper would suggest that the Florida reefs are relatively unaffected by anthropogenic N. Such results are in contrast with the study by Sammarco et al (1999), which examined a number of reefs stretching from the coast of Australia to the Great Barrier Reef, a distance of 120 km.…”
Section: Discussionmentioning
confidence: 99%
“…The nearshore reefs occur less than 5 km offshore and often experience extremely turbid waters. Although waters close to the Florida Keys tend to be slightly elevated in their nutrient concentrations and, based on the studies by Shinn et al (1994) and Lapointe et al (1990), might be expected to be affected by sewage derived from the Florida Keys, by 0.5 km, it has been shown that the nutrient concentrations of the reefal water are close to open marine conditions (Szmant and Forrester 1996). If the ␦ 15 N of organisms, such as corals, can be considered to be valid indicators of anthropogenic influence on the marine environment, then the data presented in this paper would suggest that the Florida reefs are relatively unaffected by anthropogenic N. Such results are in contrast with the study by Sammarco et al (1999), which examined a number of reefs stretching from the coast of Australia to the Great Barrier Reef, a distance of 120 km.…”
Section: Discussionmentioning
confidence: 99%
“…This is of particular concern when waters such as those off the Florida Keys are heavily utilized for recreational activity in addition to being ecologically sensitive to poor water quality, a common trait of all coral reef ecosystems. Several physical factors such as tidal pumping and the porous nature of limestone contribute to the rapid groundwater migration rates observed in many of Florida's coastal communities (145).…”
Section: Survival and Transportmentioning
confidence: 99%
“…Although little is known about groundwater input into Florida Bay, it has been shown that tidal forcing is responsible for subsurface flow and significant localized groundwater input along the Keys (Shinn et al 1994;Corbett et al 1999;Dillon et al 1999Dillon et al , 2000.…”
mentioning
confidence: 99%